MOVING OBJECT DETECTION AND TRACKING TECHNIQUES - R.YAMINI; Tevathiya, Ankit Singh; Singh, Shwetanshu (International Journal of Psychosocial Rehabilitation, 2020)
Moving object detection and tracking has become a challenging and rapidly changing task in the field of video tracking. With the greater rise in the number of applications of video surveillance in security, robot vision and monitoring traffic in the coming decade, the need of automated and self- regulated system to identify non-stationary entities has presented itself with the importance like never before. The first step towards the successful tracking is the detection, next is the identification of the position of the changing objects in the subsequent frames in the video. This paper presents a survey of various algorithms used in the process and also discus s its limitations.